2014
DOI: 10.1080/19440049.2014.941948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paste processing on residue levels of imidacloprid, pyraclostrobin, azoxystrobin and fipronil in winter jujube

Abstract: The changes of imidacloprid, pyraclostrobin, azoxystrobin and fipronil residues were studied to investigate the carryover of pesticide residues in winter jujube during paste processing. A multi-residue analytical method for winter jujube was developed based on the QuEChERS approach. The recoveries for the pesticides were between 87.5% and 116.2%. LODs ranged from 0.002 to 0.1 mg kg(-1). The processing factor (Pf) is defined as the ratio of pesticide residue concentration in the paste to that in winter jujube. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…Peng et al . demonstrated that a great proportion of pesticide residues was retained in jujube peel and can be reduced by peeling.…”
Section: Effects Of Common Household Preparationsmentioning
confidence: 99%
“…Peng et al . demonstrated that a great proportion of pesticide residues was retained in jujube peel and can be reduced by peeling.…”
Section: Effects Of Common Household Preparationsmentioning
confidence: 99%
“…4,5 Capillary electrophoresis 6 and subsequent liquid chromatography (LC) UV 7,8 and mass spectrometry (MS) [9][10][11][12][13][14] have been utilized for the determination of pyraclostrobin in different matrices, such as apple, 10 citrus, 11 pepper, 12 peanut, 13 rice, 14 grape. 9 Besides, attention has been paid to the change of pyraclostrobin in food processing such as rasin 15 and paste 16 preparation. In addition, dissipation studies have been conducted in apple, 10 pepper, 12 peanut, 13 banana, 8 grape, 9 giving half-lives of 1.6 to 1.7 days in maize, 17 3.39-4.06 days in glasshouse strawberry, 18 10.3-11.2 days in peanut, 13 17.8-25.9 days in grape.…”
Section: Introductionmentioning
confidence: 99%
“…We know that different food processing technologies will lead to different residue levels, and the disposition of the residues in various processed products [ 31 ]. The PFs lay an important role in performing a risk assessment for a pesticide under a specific treatment in specific commodity [ 9 , 32 ].…”
Section: Resultsmentioning
confidence: 99%